1993
DOI: 10.1088/0031-8949/1993/t49b/010
|View full text |Cite
|
Sign up to set email alerts
|

Quantum effects in thermal and thermo-electric transport in semiconductor nanostructures

Abstract: Current heating is used to create a micron-scale hot electron reservoir in Semiconductor nanostructures at low temperatures. This technique enables the study of quantum effects in various thermo-electric transport coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In the lower-temperature cases, the output even reverses, for example, as V G is higher than +13 V or lower than −12 V. Both the Seebeck effect and ballistic rectifying effect are expected to present in the device, and the latter is known to weaken at high-gate voltages because of high carrier concentrations. So, the output reversal is likely due to the Seebeck effect that becomes more dominant at large gate biases 14 17 .…”
Section: Resultsmentioning
confidence: 99%
“…In the lower-temperature cases, the output even reverses, for example, as V G is higher than +13 V or lower than −12 V. Both the Seebeck effect and ballistic rectifying effect are expected to present in the device, and the latter is known to weaken at high-gate voltages because of high carrier concentrations. So, the output reversal is likely due to the Seebeck effect that becomes more dominant at large gate biases 14 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, previous reports on chalcogenide materials have demonstrated that κ can be decreased significantly by nanostructuring. , Grain boundary effects allow extensive phonon scattering, which is one of the key reasons for employing nanostructured TE materials to have low κ. Almost all the synthesis techniques have focused on phonon scattering at the grain boundaries by quantum confinement effects. Apart from the quantum confinement effects, the mean free path of electrons and phonons plays a crucial role when nanostructuring is employed in these materials. As a result, a large density of interfaces are formed, which enables the preferential scattering of phonons over electrons, and thus the lattice contribution toward κ is decreased, while the carrier concentration and σ are preserved.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is always a challenge to optimize the individual parameters of σ, S and κ for thermoelectric materials due to their interdependent and conflict [7]. Up to now, besides using band engineering through tuning band convergence [4], 2 / ZT S T σ κ = quantum confinement [8,9], and effective mass [10] to maximizing S 2 σ, most successful ZT enhancement has been achieved via structural and nanostructural engineering [11] or hierarchical architecturing [3] to reduce κ.…”
Section: Introductionmentioning
confidence: 99%
“…With these potentials, it is necessary to further improve its thermoelectric performance through novel strategies, such as nanostructuring or band engineering. Especially, nanostructuring has been theoretically predicted [8] and experimentally demonstrated [5,9] that can efficiently enhance ZT of thermoelectric materials. Although there have been very success on developing bulk Cu 2 Se, significant improvement of thermoelectric performance has not been achieved in nanostructured Cu 2 Se.…”
Section: Introductionmentioning
confidence: 99%